A Novel Liquid-Liquid Extraction Technique for the Extraction and Separation of Yttrium(III) with Hexaacetato Calix[6]arene - Swamidoss, C.M.; Malkhede, D.D. (Asian Journal of Chemistry, 2010)
A method is proposed for the extraction of yttrium(III) using hexaacetato calix[6]arene. The optimum extraction conditions are evaluated from a critical study of the effect of pH, concentration of extractant, shaking time, concentration of various mineral acids used as stripping agents, different types of polar and non polar diluents and effect of diverse ions. Solvent extraction of yttrium(III) was carried out using hexaacetato calix[6]arene in xylene. Yttrium(III) is quantitatively extracted with 1 × 10-4 M of the ligand in xylene at pH 6 when equilibrated for 12 min. Yttrium in the organic phase was stripped with 4 M nitric acid and determined spectrophotometrically by the arsenazo(III) method at 660 nm. The metal loading capacity of the reagent is also studied. The extraction of Y(III) was carried out in the presence of various ions to ascertain the tolerance limit of individual ions. Yttrium was successfully separated from commonly associated metal ions. The method can be extended for the determination of yttrium in real samples.